2016
DOI: 10.1136/gutjnl-2016-312580
|View full text |Cite
|
Sign up to set email alerts
|

Human oral microbiome and prospective risk for pancreatic cancer: a population-based nested case-control study

Abstract: Objective A history of periodontal disease and the presence of circulating antibodies to selected oral pathogens have been associated with increased risk of pancreatic cancer; however, direct relationships of oral microbes with pancreatic cancer have not been evaluated in prospective studies. We examine the relationship of oral microbiota with subsequent risk of pancreatic cancer in a large nested case-control study. Design We selected 361 incident adenocarcinoma of pancreas and 371 matched controls from two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
570
6
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 611 publications
(640 citation statements)
references
References 56 publications
16
570
6
8
Order By: Relevance
“…They also found that a greater abundance of the phylum Fusobacteria was associated with decreased pancreatic cancer risk as well as its genus Leptotrichia [66]. Their finding was inconsistent with a recent cross-sectional study of eight patients, which found higher abundances of Leptotrichia and Porphyromonas in the saliva of pancreatic cancer patients compared to controls and those with other diseases, including non-cancerous pancreatic disease [18].…”
Section: Brief Additional Clinical Information On Leptotrichia Speciesmentioning
confidence: 99%
See 4 more Smart Citations
“…They also found that a greater abundance of the phylum Fusobacteria was associated with decreased pancreatic cancer risk as well as its genus Leptotrichia [66]. Their finding was inconsistent with a recent cross-sectional study of eight patients, which found higher abundances of Leptotrichia and Porphyromonas in the saliva of pancreatic cancer patients compared to controls and those with other diseases, including non-cancerous pancreatic disease [18].…”
Section: Brief Additional Clinical Information On Leptotrichia Speciesmentioning
confidence: 99%
“…They were also recovered from oral plaque of guinea pigs [21] and feces of piglets [54], dental plaque from healthy individuals, plaque and saliva from patients with various types of caries, gingivitis, chronic periodontitis, and peri-implantitis [23,2527,34,35,37,38,44,45,47,49,52,59,60,62,6669,91,94], decayed tooth surfaces and discordant caries from intact enamel surfaces [53]. Leptotrichia species were also isolated from bronchoalveolar lavage fluid, and patients with leukocytosis, hypoxemia, and dyspnea [24].…”
Section: Brief Additional Clinical Information On Leptotrichia Speciesmentioning
confidence: 99%
See 3 more Smart Citations